Use of gonadotropin-releasing hormone (GnRH) agonist trigger in fertility preservation for patients with inherited genetic disorders - Merkison, Jamie; Malcom, Carrie; Decherney, Alan (Frontiers in Endocrinology, 2022)
In patients with varying hematologic disorders (thalassemia, sickle cell anemia, aplastic anemia, etc.), inherited bone marrow failure syndromes, and immune deficiencies due to a single gene disorder, the advent of stem cell transplantation (SCT) as a treatment option has allowed for significant disease improvement, and possibly cure. This specific treatment option often requires exposure chemotherapeutic agents and sometimes whole body radiation; therefore, primary ovarian insufficient is often sequelae of the therapy. The optimization of fertility preservation protocols within this patient population is of extreme importance. This review aims to detail the use of GnRH agonist use within this patient population, within the context of fertility preservation cycles.